The Analysis of Arabic Language Textbooks for Class II Elementary School - Ilya Husna; Hidayati Azkiya; Suci Ramadhanti Febriani; Rahmawati Rahmawati; Martin Kustati (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2022)
Textbooks are one of the learning resources used in the learning process. As the main learning resource, textbooks serve as a medium for educators and students in an effort to achieve learning objectives. This study aims to describe errors in textbooks. The focus of the research was done by looking at syntactic errors, vocabulary, and writing Arabic words. The source of the data in this research is the Arabic book for Class II Madrasah Ibtidaiyah written by Sunaryo Putro published by PT. Three Series of Independent Libraries, Solo. The research method used is the method of content analysis with the analytical technique used is to record the types of errors contained in the textbook. The results showed that there were 13 errors in the textbook that the author examined with details of 3 errors in syntax, in the form of an error in the final vowel of a word that is not in accordance with its maqam i'rab, 3 errors in vocabulary (mufradat) which is the vocabulary in the book. not in accordance with the actual meaning, as well as 7 errors in writing words that do not refer to the writing of Arabic words that are good and correct, in accordance with the rules of Islamic science.